1990
DOI: 10.1523/jneurosci.10-08-02749.1990
|View full text |Cite
|
Sign up to set email alerts
|

Circadian fluctuations of period protein immunoreactivity in the CNS and the visual system of Drosophila

Abstract: When the protein encoded by the period (per) gene, which influences circadian rhythms in Drosophila melanogaster, was labeled with an anti-per antibody in adult flies sectioned at different times of day, regular fluctuations in the intensity of immunoreactivity were observed in cells of the visual system and central brain. These fluctuations persisted in constant darkness. Time courses of the changing levels of staining were altered in the per-short mutant: in light/dark cycles, the phase was earlier than in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
362
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(396 citation statements)
references
References 29 publications
(92 reference statements)
33
362
1
Order By: Relevance
“…Later, it was shown that in per S mutants, the accumulation profile and nuclear clearance of dPER are advanced (Zerr et al 1990;Edery et al 1994), whereas in per L flies, the nuclear entry of the PER protein is delayed (Curtin et al 1995). Similar effects were observed in dbt mutants (e.g., dbt S and dbt L ) Price et al 1998).…”
Section: Circadian Phenotypes With Altered Per Phosphorylationmentioning
confidence: 79%
“…Later, it was shown that in per S mutants, the accumulation profile and nuclear clearance of dPER are advanced (Zerr et al 1990;Edery et al 1994), whereas in per L flies, the nuclear entry of the PER protein is delayed (Curtin et al 1995). Similar effects were observed in dbt mutants (e.g., dbt S and dbt L ) Price et al 1998).…”
Section: Circadian Phenotypes With Altered Per Phosphorylationmentioning
confidence: 79%
“…Therefore, change in degradation rate of PER has also been used in some models (Scheper, Klinkenberg et al 1999;Lema, Golombek et al 2000;Smolen, Hardin et al 2004). Indeed, experimental findings have shown that tim 01 mutants inducing an absence of TIM lead to a substantial lowering of PER abundance (Vosshall, Price et al 1994;Price, Dembinska et al 1995), an effect that happens to be similar to the result of exposing flies to constant light (Zerr, Hall et al 1990;Price, Dembinska et al 1995). Because we did not include the detailed translocation mechanisms of PER and TIM into the nucleus, as well as associated Sgg-dependent TIM phosphorylation and CK2-dependent PER phosphorylation processes in the model (Shafer, Rosbash et al 2002), we simulated the effect of light by increasing the degradation rates of both TIM and PER.…”
Section: Response Of the Circadian Clock To Lightmentioning
confidence: 97%
“…After initial activation of per and tim expression, there is a 4 h -6 h delay between the peak concentrations of per and tim mRNAs and that of PER and TIM proteins (Zerr, Hall et al 1990;Zeng, Qian et al 1996). As a result, CLK/CYC can continue to activate transcription of per and tim genes, while PER and TIM proteins accumulate in the cytoplasm.…”
Section: Review Of Molecular Basis Of the Drosophila Circadian Clockmentioning
confidence: 99%
“…This suggests that PDF-negative clock neurons (including the LPN) may be more important. To test this, disco mutant flies, which lack the PDF neurons and the dorsal lateral neurons (LNd), but not the dorsal neurons (DN) and the LPNs (Zerr et al 1990;Kaneko and Hall 2000;Yoshii et al 2005), were analyzed in temperature cycles. They were found to exhibit only weakly synchronized behavioral rhythms and also exhibited synchronized PER expression in LPN and DN cells (Yoshii et al 2005), suggesting that these neurons mediate at least some aspects of temperature-entrained behavior.…”
Section: Neural Substratesmentioning
confidence: 99%